Serum Albumin and Circulating Metabolites and Risk of Venous Thromboembolism: A Two-Sample Mendelian Randomization Study - Liu, Zhengye; Mi, Jiarui (Frontiers in Nutrition, 2021)
Background and Aims: Previous observational studies indicated that serum albumin levels and circulating metabolites are associated with high risk of venous thromboembolism (VTE). However, whether these observations reflect causality remained unclear. Hence, we conducted a two-sample Mendelian randomization analysis to evaluate the causal associations of serum albumin and circulating metabolites with the risk of VTE. Methods and Results: Summary statistics of genetic instruments proxying serum albumin, total protein and common circulating metabolites were extracted from genome-wide association studies in European ancestry. Summary-level results of age‐ and sex‐adjusted estimates for associations of the instruments with VTE were derived from FinnGen consortium. We used inverse-variance weighted (IVW) method as the primary analysis for univariable MR. Sensitivity analyses were perform to detect horizontal pleiotropy and outliers. Genetically proxied high serum albumin and total protein levels were suggestive protective factor of VTE, with odds ratio (OR) equal to 0.69 (confidence interval [CI] 0.54-0.89, p = 4.7×10–3) and 0.76 (CI 0.61-0.95, p = 0.015) respectively. Genetically proxied low monounsaturated fatty acids and the ratio of monounsaturated fatty acid to total fatty acid are causally associated with increased risk of VTE, with ORs equal to 0.89 (CI 0.80-0.99, p = 0.031) and 0.85 (CI 0.78-0.94, p = 9.92×10–4) respectively. There is no indication of causal associations between other circulating metabolites and the risk of VTE. Conclusions: Genetically liability to low serum albumin and total protein levels, low MUFAs and ratio of MUFAs to total fatty acids are associated with higher risk of VTE.